2008
DOI: 10.1016/j.paid.2007.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Mental toughness, optimism, pessimism, and coping among athletes

Abstract: The concept of mental toughness is widely used, but empirical evidence is required to fully understand this construct and its related variables. The purpose of this paper was to explore the relationship between: (a) mental toughness and coping, (b) mental toughness and optimism, and (c) coping and optimism. Participants were 677 athletes (male 454; female 223) aged between 15 and 58 years (M age = 22.66 years, SD = 7.20). Mental toughness correlated significantly with 8 of the 10 coping subscales and optimism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
196
2
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(225 citation statements)
references
References 33 publications
16
196
2
11
Order By: Relevance
“…Results of the regression analysis did find that challenge, emotional control (negative weighting) and confidence in abilities (negative weighting) were significant predictors of preference for social support, although together, these subscales only accounted for approximately 8% of the variance in social support. Nicholls et al (2008) had suggested that seeking social support was incompatible with mental toughness, although recent qualitative research has found social support to be important in the development of mental toughness (Connaughton, Wadey, Hanton & Jones, 2008). The present results suggest that total mental toughness was not significantly related to a preference for social support, positive feedback, democratic or autocratic behaviours.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Results of the regression analysis did find that challenge, emotional control (negative weighting) and confidence in abilities (negative weighting) were significant predictors of preference for social support, although together, these subscales only accounted for approximately 8% of the variance in social support. Nicholls et al (2008) had suggested that seeking social support was incompatible with mental toughness, although recent qualitative research has found social support to be important in the development of mental toughness (Connaughton, Wadey, Hanton & Jones, 2008). The present results suggest that total mental toughness was not significantly related to a preference for social support, positive feedback, democratic or autocratic behaviours.…”
Section: Discussioncontrasting
confidence: 77%
“…Responses are made to the 48-items on a 5-point Likert scale ranging from (1) strongly disagree, to (5) strongly agree. The MTQ48 has an overall testretest coefficient of 0.9, and previous studies have found high alpha coefficients for the MTQ48 (Nicholls et al, 2008). The psychometric development of the MTQ48 (cf.…”
Section: Mental Toughnessmentioning
confidence: 95%
“…While qualitative research helped to identify some of the key attributes of mentally tough athletes, much less attention was given to issues of measurement (Crust, 2008;Sheard, Golby, & van Wersch, 2009). However, Clough et al (2002) produced an instrument that has since been used in numerous studies (i.e., Crust & Clough, 2005;Kaiseler, Polman, & Nicholls;Nicholls, Polman, Levy & Backhouse, 2008). Despite much published research using the Mental Toughness Questionnaire 48 (MTQ48; Clough et al), some researchers (i.e., Sheard et al, 2009) have been critical of the measure on two counts: First, the conceptualization that underpins the MTQ48; and second, the lack of independent scrutiny of the factor structure.…”
Section: Introductionmentioning
confidence: 99%
“…Work by Crust and Clough (2005) supported construct validity of the MTQ48 with significant relations found between MTQ48 scores and pain tolerance. Research has also found significant relations between MTQ48 scores, optimism and coping skills (Nicholls et al, 2008). In terms of reliability, the overall internal consistency of the MTQ48 has generally been reported at 0.9 or above (i.e., Kaiseler et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nicholls, Polman, Levy, and Backhouse (2008) found that optimism and pessimism were significantly correlated with eight coping constructs, (e.g., mental imagery, effort expenditure, thought control). Researchers in some Arab countries as well as through cross-culture studies (western vs. non-western) found that optimism and pessimism were significantly correlated with depression and anxiety (Abdel-Khalek, & Laster, 2006;Abdel-Khalek, & Maltby, 2008;Abu Hilal, 2006;Alansari, & Kazem, 2008;Sheier, Carver, & Bridges, 1994).…”
Section: Introductionmentioning
confidence: 99%